2014
DOI: 10.1521/psyc.2014.77.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Previous Exposure to the World Trade Center Terrorist Attack and Posttraumatic Symptoms Among Older Adults Following Hurricane Sandy

Abstract: When confronted by a natural disaster, American older adults are generally resilient. Supporting the inoculation hypothesis, resilience of older adults may be partly related to the strength successfully extracted from previous exposure to adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 34 publications
8
39
1
Order By: Relevance
“…Recent studies suggest that prevalence of hurricane-related PTSD is high among those impacted by Sandy. For instance, an online survey of 1,000 participants conducted one month post-Sandy found PTSD symptoms in 23.6% of persons from Sandy affected areas (Palgi et al, 2014), and PTSD symptoms were positively related to degree of Sandy exposure (Shrira, Palgi, Hamama-Raz, Goodwin, & Ben- Ezra, 2014). Another cross-sectional telephone survey of 200 adults conducted 6–8 months post-Sandy among individuals residing in communities along New Jersey’s coastline found that 14.5% of residents screened positive for PTSD; high Sandy exposure strongly predicted adverse mental health status (Boscarino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that prevalence of hurricane-related PTSD is high among those impacted by Sandy. For instance, an online survey of 1,000 participants conducted one month post-Sandy found PTSD symptoms in 23.6% of persons from Sandy affected areas (Palgi et al, 2014), and PTSD symptoms were positively related to degree of Sandy exposure (Shrira, Palgi, Hamama-Raz, Goodwin, & Ben- Ezra, 2014). Another cross-sectional telephone survey of 200 adults conducted 6–8 months post-Sandy among individuals residing in communities along New Jersey’s coastline found that 14.5% of residents screened positive for PTSD; high Sandy exposure strongly predicted adverse mental health status (Boscarino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prior studies have found that retrospective reports of low social support (Acierno et al, 2007; Boscarino et al, 2013) and recollections of prior disasters including earlier hurricanes or the September 11, 2001 (9/11) disaster (Palgi et al, 2014; Shrira et al, 2014) significantly increase the likelihood of hurricane-related PTSD. However, these studies do not provide a temporal relationship between exposure and subsequent PTSD or account for the longitudinal influence of social support.…”
Section: Introductionmentioning
confidence: 99%
“…We will investigate whether older adults who have not been previously exposed to trauma or have experienced a lower level of PTLE find it more difficult to cope with first-time traumatic events, such as war or terror. Unlike older adults, younger adults may exploit their social support or their coping flexibility when facing trauma, rather than using their emotional regulation system (Shrira et al, 2014). Therefore, it is expected that a strong association between age and PTSD will be found among those who report lower levels of previous PTLE.…”
Section: Introductionmentioning
confidence: 99%
“…As elsewhere, women proved particularly vulnerable to distress after each of the attacks (Bleich et al, 2003). Younger people were more distressed, potentially the result of maturation processes that generally favour older adults (Shrira et al, 2014). Physical location was related to distress, with those in the 'bulls eye' of the attacks (Parisians) more distressed regardless of the event.…”
Section: Discussionmentioning
confidence: 67%